Cytogenetic evaluation of chili (Capsicum spp., Solanaceae) genotypes cultivated in Valle del Cauca, Colombia (2017)
The genus Capsicum comprises a large group of hot and sweet peppers, with different morphological varieties and degree of fruits pungency. Due to its active principles is widely used in cooking and in traditional medicine, being sold in large worldwide. In order to provide cytogenetic information which supporting plant breeding programs, this study aimed to analyze the meiotic behavior, chromosome number and pollen viability of the three species of greater economic importance of Capsicum (C. annuum, C. frutescens and C. chinense). Therefore, fruits and flower buds were collected from the Experimental Center of the Universidad Nacional de Colombia, campus Palmira- CEUNP to the corresponding mitotic, meiosis and pollen viability analysis. Plants presented different meiotic abnormalities, where all can disrupt the process of meiosis cell division, creating unbalanced chromosome numbers and varied pollen fertility. Chromosome number variation, checking 2n=2x=24, 2n=2x=26, 2n=4x=48 to 2n=6x=72 chromosomes also occurred. A low degree of non-viable pollen grains was observed for C. frutescens, so these accession should not considered as a parental for plant breeding programs.